2023
DOI: 10.2196/46148
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Patient Use and Satisfaction With Synchronous Telemental Health Services During the COVID-19 Pandemic: Systematic Review

Ariana Neumann,
Hans-Helmut König,
Josephine Bokermann
et al.

Abstract: Background Several recent studies examined patient use and satisfaction with synchronous telemental health services in response to the widespread implementation during the COVID-19 pandemic. However, a systematic review of recent literature on the determinants of these outcomes is missing. Objective The aim of this systematic review was to give an extensive overview of the literature on and highlight the influential determinants of patient use and satis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Telehealth accelerated during the COVID-19 pandemic and is likely to persist. Although telehealth is accepted by most psychiatric patients, individuals with primary or co-occurring serious mental illness (SMI; ie, psychotic spectrum disorders and bipolar disorders) show lower engagement [ 1 2 ] and are less likely to use video-based services [ 3 , 4 ] than other diagnostic groups. A systematic review found that individuals with (vs without) SMI use telehealth at lower rates, despite much higher in-person mental health care (MH) use among individuals with SMI [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telehealth accelerated during the COVID-19 pandemic and is likely to persist. Although telehealth is accepted by most psychiatric patients, individuals with primary or co-occurring serious mental illness (SMI; ie, psychotic spectrum disorders and bipolar disorders) show lower engagement [ 1 2 ] and are less likely to use video-based services [ 3 , 4 ] than other diagnostic groups. A systematic review found that individuals with (vs without) SMI use telehealth at lower rates, despite much higher in-person mental health care (MH) use among individuals with SMI [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although telehealth is accepted by most psychiatric patients, individuals with primary or co-occurring serious mental illness (SMI; ie, psychotic spectrum disorders and bipolar disorders) show lower engagement [ 1 2 ] and are less likely to use video-based services [ 3 , 4 ] than other diagnostic groups. A systematic review found that individuals with (vs without) SMI use telehealth at lower rates, despite much higher in-person mental health care (MH) use among individuals with SMI [ 2 ]. A study of patients with SMI who use telehealth during the pandemic found that, although many patients with SMI maintained engagement, individuals with schizophrenia were the least likely to engage in telehealth [ 3 ].…”
Section: Introductionmentioning
confidence: 99%